Mortality in pulmonary arterial hypertension: prediction by the 2015 European pulmonary hypertension guidelines risk stratification model - Hoeper, Marius M.; Kramer, Tilmann; Pan, Zixuan; Eichstaedt, Christina A.; Spiesshoefer, Jens; Benjamin, Nicola; Olsson, Karen M.; Meyer, Katrin; Vizza, Carmine Dario; Vonk-Noordegraaf, Anton; Distler, Oliver; Opitz, Christian; et al. (The European respiratory journal, 2017)
The 2015 European pulmonary hypertension (PH) guidelines propose a risk stratification strategy for patients with pulmonary arterial hypertension (PAH). Low-, intermediate- and high-risk strata are defined by estimated 1-year mortality risks of <5%, 5–10% and >10%, respectively. This risk assessment strategy awaits validation. We analysed data from patients with newly diagnosed PAH enrolled into COMPERA (Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension), a European-based PH registry. An abbreviated version of the risk assessment strategy proposed by the European PH guidelines was applied, using the following variables: World Health Organization functional class, 6-min walking distance, brain natriuretic peptide or its N-terminal fragment, right atrial pressure, cardiac index and mixed venous oxygen saturation. Data from 1588 patients were analysed. Mortality rates were significantly different between the three risk strata (p<0.001 for all comparisons). In the entire patient population, the observed mortality rates 1 year after diagnosis were 2.8% in the low-risk cohort (n=196), 9.9% in the intermediate-risk cohort (n=1116) and 21.2% in the high-risk cohort (n=276). In addition, the risk assessment strategy proved valid at follow-up and in major PAH subgroups. An abbreviated version of the risk assessment strategy proposed by the current European PH guidelines provides accurate mortality estimates in patients with PAH.